Espectroscopia vibracional em cristais de d-alanina e dl-alanina sob condições extremas - Belo, Ezequiel de Andrade (2013)
In this work the vibrational behavior of single crystals of D-alanine (DALA) and DLalanine (DLA) under extreme conditions of temperature and pressure have been studied. By doing so, have been used infrared and Raman spectroscopy. The infrared spectra for DALA crystal were measured between 400 cm-1 to 3200 cm-1 from room temperature up to 100 K and the results obtained are similar to those reported in literature for the Lalanine (LALA) and DLA crystals small differences were observed and discussed in the text. Raman spectra for DALA crystal were measured between 30 cm-1 to 3200 cm-1 with temperature ranging from 295 K to 20 K in six different polarizations using the backscattering geometry. The results illustrate the complexity of the phonon spectrum near the point q = 0 and such results indicate the existence of two phase transitions regions located at 230 ± 20 K and 150 ± 20 K. Raman spectra for DALA crystal were also measured by subjecting the sample to pressures up to 14 GPa some spectral ranges were analyzed and the results show, once more, two possible phase transitions located in the pressure range from 1.5 to 1.8 GPa and from 3.6 to 4.4 GPa. Raman spectra for DLA crystal were measured between 50 cm-1 to 3100 cm-1 from atmospheric pressure up to 18 GPa, changes observed in these spectra leads us to conjecture three phase transitions undergone by the DLA crystal. These structural transitions are associated to conformational changes that occur at pressures slightly lower than those related to structural changes; the first of them takes place between 1.7 GPa and 2.3 GPa. Right above, between 4 GPa and 4.6 GPa it is noticed changes that precede the second structural transition that occurs between 6 GPa and 7GPa. Finally, changes in the lattice modes frequency between 6.11 GPa and 13.2 GPa were designated with being a third phase transition. It is noteworthy that returning to ambient conditions in both pressure and temperature experiments the spectra obtained previously were recovered which indicates the reversibility of the phase transitions studied in this thesis.